2008
DOI: 10.22358/jafs/66476/2008
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of pelleted compound feeds under varying storage conditions as influenced by purity and concentration of glycerol from biodiesel production

Abstract: The effects of concentrates, in which glycerol plus soyabean meal replaced wheat, on physical, chemical and hygienic pellet quality characteristics were investigated. Three purities of glycerol were used, refl ecting different stages of the biodiesel production process. Glycerol inclusion levels were 50, 100 and 150 g/kg concentrate dry matter (DM). Concentrates were stored under good (15°C, 60% relative humidity) or bad (20°C, 70% relative humidity) environmental conditions and for 4 or 8 weeks. Chemical qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Jenkins [ 18 ] reported that inclusion of lipids in ruminant diets could negatively affect the NDF digestibility and animal performance. In addition, glycerol supplementation affects negatively the digestion of the more fibrous fraction of the feed [ 19 ]. Thus, the association of CGWVO with higher content of crude fat in diets decreased the DMI and digestibility by the animals.…”
Section: Resultsmentioning
confidence: 99%
“…Jenkins [ 18 ] reported that inclusion of lipids in ruminant diets could negatively affect the NDF digestibility and animal performance. In addition, glycerol supplementation affects negatively the digestion of the more fibrous fraction of the feed [ 19 ]. Thus, the association of CGWVO with higher content of crude fat in diets decreased the DMI and digestibility by the animals.…”
Section: Resultsmentioning
confidence: 99%
“…Pelleted feeds have been successfully used for animals. Pelleting improves the palatability, density, and quality of feedstuff [ 11 ]. Pellet diets could enhance nutrient digestibility and fermentation in the rumen [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strategic feeding of ruminants with pellets containing phytochemical compounds is one approach that could enhance rumen fermentation and decrease greenhouse gases. Furthermore, pelleted feeds enhance the acceptability, density and quality of diets [2]. Previous studies demonstrated that supplementation with pelleting plants rich in saponins and tannins such as raw banana [3], mangosteen ( Garcinia mangostana ) peel [4], Leucaena leaf [5] and banana flower [6] could improve ruminal propionic acid concentration and microbial protein synthesis while reducing the protozoal population and ruminal methane (CH 4 ) gas production.…”
Section: Introductionmentioning
confidence: 99%